2020
DOI: 10.1136/jech-2019-212981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased minimum wages by unemployment rate on suicide in the USA

Abstract: BackgroundSocial welfare policies such as the minimum wage can affect population health, though the impact may differ by the level of unemployment experienced by society at a given time.MethodsWe ran difference-in-differences models using monthly data from all 50 states and Washington, DC from 1990 to 2015. We used educational attainment to define treatment and control groups. The exposure was the difference between state and federal minimum wage in US$2015, defined both by the date the state law became effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 22 publications
4
62
0
3
Order By: Relevance
“…For instance, lack of job opportunities and an increase in hopelessness and despair have been implicated in the marked increase in mortality among middle‐aged, white Americans 181 ; an increased risk of depression among young people 182 and adults 180 ; and an increased likelihood of health problems among African Americans 182 . Depression rates in the United States have been shown to be higher among non‐Hispanic Blacks and Hispanics, who are more likely to be in lower‐wage (lower‐skilled) jobs 183 . Conversely, employability—the ability of a person to find and maintain employment, measured by proxies such as the skills of the worker—has been demonstrated to substantially moderate the effects of unemployment and job insecurity on life satisfaction and mental health 184 .…”
Section: Cdc/niosh Future Of Work Initiative Priority Topicsmentioning
confidence: 99%
“…For instance, lack of job opportunities and an increase in hopelessness and despair have been implicated in the marked increase in mortality among middle‐aged, white Americans 181 ; an increased risk of depression among young people 182 and adults 180 ; and an increased likelihood of health problems among African Americans 182 . Depression rates in the United States have been shown to be higher among non‐Hispanic Blacks and Hispanics, who are more likely to be in lower‐wage (lower‐skilled) jobs 183 . Conversely, employability—the ability of a person to find and maintain employment, measured by proxies such as the skills of the worker—has been demonstrated to substantially moderate the effects of unemployment and job insecurity on life satisfaction and mental health 184 .…”
Section: Cdc/niosh Future Of Work Initiative Priority Topicsmentioning
confidence: 99%
“…A novel contribution of this work by Kaufman et al concerns modification of the relationship between the minimum wage and suicide by the unemployment rate 1. Research generally supports that minimum wage increases do not adversely affect employment,4 6 and this work highlights that minimum wage may be particularly important as a protective factor under conditions of higher unemployment.…”
mentioning
confidence: 79%
“…Kaufman and colleagues have considered the relationship between minimum wage and suicide mortality in the USA 1. Overall, they found that a dollar increase in the minimum wage was related to a meaningful 3.4% decrease in suicide mortality for those of lower educational attainment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, adult women who became pregnant and experienced an increase in the minimum wage had a reduced likelihood of smoking and fewer low birth weight babies. Increases in state-level minimum wages are associated with decreased infant mortality, suicide rates, and heart disease death rates (Kaufman et al 2020;Komro et al 2016;Van Dyke, Komro, Shah et al 2018).…”
Section: Increasing the Minimum Wagementioning
confidence: 99%